Does green entrepreneurial intention persuade an individual to contribute to the sustainable green economy? - Hasan Polas, Mohammad Rashed; Hossain, Mohammad Imtiaz; Tabash, Mosab I.; Karim, Asif Mahbub; Dad, Allah; Ong, Tze San (International Research Association, 2020)
The present study looked to foresee the intention toward green entrepreneurship among the Gen Z. The study applied quantitative analysis using a sample of 285 among Gen Z who were students of business administration in five private and public universities at Dhaka in Bangladesh. Which individuals' level factors are important for becoming a green entrepreneur among Gen Z? To answer this question, we examined the direct impact of sustainability orientation, sustainability education and sustainability attitude with green entrepreneurial intention. Furthermore, we tested the indirect effects of these three factors through perceived feasibility. The outcomes are acquired by applying Smart PLS 3.0 (SEM). This study claims that a positive and significant relationship remains between an individual's sustainability orientation, sustainability education and sustainability attitude with their green entrepreneurial intention. Furthermore, this study also reveals that an individual's perceived feasibility mediates the relationship between their sustainability orientation, sustainability education with their green entrepreneurial intention. Moreover, this study again claims that perceived feasibility doesn’t mediate the relationship between individual’s sustainability attitude and their green entrepreneurial intention. Furthermore, the study's outcomes would bolster the government, policymakers, and university authorities in creating a tailor‐made awareness program through building a curriculum that could offer more prominent intention toward green and sustainable education. Besides, the results may lead to giving a superior living place to people in the future around the world.